TEKNIK PENGAJARAN KETERAMPILAN BERBICARA BAHASA INGGRIS DI SMP ISLAM TERPADU UKHUWAH BANJARMASIN TAHUN AJARAN 2014 / 2015 - Perdana, Iwan (Vidya Karya Jurnal Kependidikan, 2015)
The purpose of this research is to know the technique of teaching speaking at SMP Islam Terpadu Ukhuwah Banjarmasin. The researcher used qualitative design-multisite type and collected data through participant observation, interview and document. The gotten result are: (1) guided speaking, short conversation, role play and rubric, (2) the use of techniques are depend on the studentsâ level and their ability, (3) those techniques are implemented based on its steps, and (4) there is no better or worse technique among of them, each technique will give best result depends on the studentsâ level and their ability.